Suffix -ota (-eta) in Ukrainian language XI–XIII centuries (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The origin of the suffix -ота (-ета) is revealed, the function of these formants is described in the old Russian-Ukrainian language at the level of word forming and lexical word forming types. The documented derivatives of XI–XIIІ centuries were created from adjectives, and rarely from verbs, nouns and other parts of the language. Suffix -ота (-ета) in semantic terms continues the tradition of the Old Slavic language: with this formant mainly abstract names of qualities and characteristics were created that might acquire different abstract meaning or were subject to concretization or specification.Overview derivatives with the suffix -ota (-eta) gives reason to believe that the formant performing similar functions as in Proto-Slavic language, he participated in the creation of abstract names of adjectives, verbs and nouns with a fairly wide range of lexical and structural word types. In nouns often deals with the points observed the development of secondary importance, with secondary semantics often goes beyond the abstract. Only in rare cases have substantyvy -ota on the specific value, often this semantics is secondary. In some cases betrays a tendency entry formant     -ota uvyraznyuvalnoyi function.
Keywords: -ота (-ета) suffix; lexical word forming types; the Old Russian-Ukrainian language; substantivizing of adjectives; names of qualities and characteristics; specification of abstract names